Developing and integrating nursing competence through authentic technology-enhanced clinical simulation education: Pedagogies for reconceptualising the theory-practice gap. (May 2019) - Weeks, Keith W.; Coben, Diana; O'Neill, David; Jones, Alan; Weeks, Alex; Brown, Matt; Pontin, David
Abstract: The aim of this review and discussion paper is to advance the debate on competence in nursing, simulation education, and literacy in simulation education pedagogy. Building on our previous patient-safety critical translational research work on drug dosage calculation-competence modelling, and safeMedicate ® virtual learning and diagnostic assessment environment design, we introduce three new concepts. First, we re-conceptualise the cognitive and physical modalities of a theory-practice gap, created by the traditional organisation of health professional education practice. Second, that simulated clinical environments occupy the liminal spaces between the ordered, symbolic and abstract world of the classroom, and the situated, messy world of clinical healthcare practice. Third, technology-enhanced boundary objects (TEBOs) function as simulation pedagogy modalities that (a) support students' transition across the liminal space and boundaries between classroom and practice setting, and (b) support competence development and integration in nursing. We use a constructivist-based clinical simulation education model as a guiding pedagogical framework for applying TEBOs and an integrated nursing competence model. The e-version of the paper has embedded animation and illustrative video content to demonstrate these constructivist principles, using technology and computer animation to make complex education ideas accessible to experienced educators and clinicians, early-stage educators, and nursing and healthcare students.